The height leadership advantage in men and women: Testing evolutionary psychology predictions about the perceptions of tall leaders. (January 2013) - Blaker, Nancy M.; Rompa, Irene; Dessing, Inge H.; Vriend, Anne F.; Herschberg, Channah; van Vugt, Mark
Research suggests that tall individuals have an advantage over short individuals in terms of status, prestige, and leadership, though it is not clear why. Applying an evolutionary psychology perspective, we predicted that taller individuals are seen as more leader-like because they are perceived as more dominant, healthy, and intelligent. Being fit and physically imposing were arguably important leadership qualities in ancestral human environments—perhaps especially for males—where being a leader entailed considerable physical risks. In line with our expectations, our results demonstrate that by manipulating an individual's stature height positively influences leadership perception for both men and women, though the effect is stronger for men. For male leaders this height leadership advantage is mediated by their perceived dominance, health, and intelligence; while for female leaders this effect is only mediated by perceived intelligence.